Analisis Implementasi Manajamen Administrasi Sekolah pada SD Satit Phatnawitya Thailand - Nurhakiki; Isra Hayati (Economic Reviews Journal, 2024)
School Administration is a process of managing and organizing activities within a school environment with the aim of achieving efficiency and effectiveness in organizing education. School administration involves various aspects such as planning, organizing, implementing, and supervising various activities within the school. Therefore, the purpose of this study is to find out in depth about the implementation of school administration management at SD Satit Phatnawitya Thailand. The approach used is to use a qualitative method, namely research used to investigate, describe, explain, find the quality or specialty of social influences that cannot be explained, measured or described through a quantitative approach with data collection techniques using observation and interview techniques. The conclusion is that this study shows that the implementation of a management system in supporting administrative services at SD Satit Phatnawitya Thailand has been carried out well byutilizing all facilities/means and infrastructure as a stepping stone in optimizing the implementation of a management information system. Efforts to improve the quality of education have increased because they are supported by various administrative services that have been implemented at SD Satit Phatnawitya Thailand which can help students in their daily teaching and learning activities.